2019
DOI: 10.1177/1550059419876525
|View full text |Cite
|
Sign up to set email alerts
|

Phase Space Reconstruction of EEG Signals for Classification of ADHD and Control Adults

Abstract: Attention deficit hyperactivity disorder (ADHD) is a childhood behavioral disorder that can persist into adulthood. Electroencephalography (EEG) plays a significant role in assessing the neurophysiology of ADHD because of its ability to reveal complex brain activity. The present study proposes an EEG-based diagnosis system using the phase space reconstruction technique to classify ADHD and control adults. Electric activity is recorded for 47 ADHD and 50 control adults during the eyes-open, eyes-closed, and Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…15,16 In 2019, Kaur et al used SVM method to predict ADHD in accordance with electroencephalography data, and the prediction accuracy reached 93.3%, which was higher than the accuracy obtained in this study. 17 This finding suggests that in the future, the diagnosis of ADHD should be a comprehensive reference for a variety of assessment results.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In 2019, Kaur et al used SVM method to predict ADHD in accordance with electroencephalography data, and the prediction accuracy reached 93.3%, which was higher than the accuracy obtained in this study. 17 This finding suggests that in the future, the diagnosis of ADHD should be a comprehensive reference for a variety of assessment results.…”
Section: Discussionmentioning
confidence: 99%
“…The tasks presented were in studies that were organized into six groups: ER (15%), mental workload (MWL) (18%), MI (20%), SD (19%), sleep stage scoring (SS) (7%), and diagnosis of neurodegenerative diseases (ND), including Alzheimer’s disease (AD), Parkinson’s disease (PD), and schizophrenia (SZ) (9%). Other studies (12%) focused on ERP [ 47 , 149 , 150 , 151 , 152 ], anxiety and stress [ 153 , 154 ], depression [ 33 , 66 , 155 ], the detection of alcoholism [ 156 ], auditory diseases [ 157 ], attention deficit hyperactivity disorder [ 158 ], sleep apnea [ 159 ], and the classification of creativity [ 160 ]. In recent years, the application of supervised ML and DL models in MI and ER has gained significant attention, despite decades-long research studies already in progress in these fields ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“… 6 channels Keirn and Aunon database WT/EMD SVM KNN Accuracy = 80–100 [ 184 ] 2020 SD 10 subj. BONN database FT/WT SVM KNN Accuracy = 100 [ 158 ] 2020 ADHD 97 subj. 19 channels Own database PSR NDC EPNN SVM Accuracy = 100 [ 177 ] 2020 MI 5 subj.…”
Section: Table A1mentioning
confidence: 99%
“…The focus of this study was on ERP data because the event-related data are more sensitive and provide better performance than spontaneous EEG data recorded while the participants are at a resting state. Various studies have shown that patients with ADHD display brain alterations using ERP attributes (Müller et al 2019 ; Lenartowicz and Loo 2014 ; Öztoprak et al 2017 ; Li et al 2018b ; Kaur et al 2020 ). However, the pre-processing method may also improve the performance of EEG data.…”
Section: Discussionmentioning
confidence: 99%